Analysis of the Needs for the Development of a Work Environment-based Occupational Safety and Health Training Model in the Construction Industry - Triwati, Ika; Jamaluddin, Jamaluddin; Purnamawati, Purnamawati (International Journal of Education, Vocational and Social Science, 2024)
Occupational Health and Safety in the construction industry is not only a matter of meeting government regulations or international standards, but also an effort to reduce the number of frequent work accidents. this study aims to describe the analysis of the need for the implementation of health and safety in the construction industry to develop a work environment-based health and safety training model in the construction industry. This study uses a quantitative approach with a survey method to identify relevant health and safety training needs based on the conditions of the work environment at PT. XYZ. The design of this study is descriptive, aiming to clearly and objectively describe the needs of health and safety training based on the variables that exist in the work environment of PT. XYZ. This study uses a purposive sampling technique, selecting samples representing various divisions or different parts of the company, such as field workers, technicians, and supervisors totaling 32 people. The data collection time is adjusted to the company's operational schedule to minimize disruption to work activities. The results of this study will be used to develop a health and safety training model that is tailored to the needs identified in the research. The results of the research obtained needs analysis information including: (1) Analysis of the implementation of health and safety consisting of policies, namely Strengthening the supervision system for the implementation of health and safety, Conduct ongoing training with post-training evaluations to ensure employee understanding and compliance with health and safety, and Develop an incident reporting system that is easily accessible and protected from sanctions so that employees feel comfortable reporting any incidents; (2) There are several job risks that can be experienced by workers. The description is Excavation work is vulnerable to the risk of landslides or landslides, The work floor casting work involves the use of heavy equipment such as concrete mixers, transport trucks, and concrete vibrators. and Iron installation work is often carried out at construction sites with heights and (3) The results of the questionnaire related to the use of PPE for workers obtained information on workers using PPE by 28%; and workers do not use PPE by 72%. Thus, the tendency to use PPE for workers at PT. XYZ is in the category of not using.